Pengaruh Variasi Temperatur Operasi Terhadap Kandungan Syngas DRFB Berbahan Bakar RDF - Maulana, I Putu Handika; Winaya, I Nyoman Suprapta; Darma, I Wayan Arya (Teknik Desain Mekanika; Vol 10 No 4 (2022): Oktober 2022 : Teknik Desain Mekanika, 2022)
Abstract DRFB is a type of gasification reactor that has two reactors, a gasification reactor and a combustion reactor. In the combustion reactor, a fluidization process occurs where the fuel and bed material circulate like a fluid and then driven by a blower that has been heated with a constant air velocity of 9 m/s. In this study, the operating temperature variations in the combustion reactor are 550 C, 600 C, 650 C, 700 C. In this study there are several control variables such as using silica sand as bed material, the fuel used is RDF and the agent gas used is H2O. The results of this study will show the best results from the syngas content with variations in operating temperature in a dual fluidized bed reactor. Keywords: Fluidization, Temperature, DRFB